Testing spoken language - Underhill, Nic (Cambridge University Press, 1987)
This is a practical guide to designing and using oral tests of language ability. It is for teachers, testers, course designers and educational planners. The organisation follows the sequence of stages in which a new testing programme would logically be carried out. It takes the reader through the testing process, giving practical examples and discussing the issues involved at each stage. Testing Spoken Language removes testing from the realm of the specialist and presents it as an integral part of a language learning programme. It describes the range of test-types and discusses their suitability for different aims and resources; lists over fifty oral test techniques and variations, with comments on each; integrates the marking system into the process of test design; and provides suggestions for monitoring and improving a test once it is in use